The Pivotal Role of Oxidative Stress in the Pathophysiology of Cardiovascular-Renal Remodeling in Kidney Disease - Verdiana Ravarotto; Giovanni Bertoldi; Georgie Innico; Laura Gobbi; Lorenzo A. Calò (MDPI AG, 2021)
The excessive activation of the renin-angiotensin system in kidney disease leads to alteration of intracellular pathways which concur altogether to the induction of cardiovascular and renal remodeling, exposing these patients since the very beginning of the renal injury to chronic kidney disease and progression to end stage renal disease, a very harmful and life threatening clinical condition. Oxidative stress plays a pivotal role in the pathophysiology of renal injury and cardiovascular-renal remodeling, the long-term consequence of its effect. This review will examine the role of oxidative stress in the most significant pathways involved in cardiovascular and renal remodeling with a focus on the detrimental effects of oxidative stress-mediated renal abnormalities on the progression of the disease and of its complications. Food for thoughts on possible therapeutic target are proposed on the basis of experimental evidences.